(In)Segurança alimentar entre agricultores familiares orgânicos da zona da mata setentrional pernambucana - Freitas, Rubenice Maria de (2021)
This research was developed in the state of Pernambuco, precisely in the zone of the northern forest, in the municipality of Lagoa de Itenga, where the association of agroecological producers and residents of the communities of Imbé, Marreco and neighboring sites (so) is located. This association is the only one in the current delimitation of the Northern Forest Zone, which includes the registration of linked organic producers and registered the organization of social control (OCS). Considering the importance of organic agriculture for this public and the expansion of it in Brazil, many questions have been raised, among them the production of food and quality food, the emergence of market demand and the accessibility of food by the population according to The price, and these issues are related to the problem of food security (IN). In view of the foregoing, this research aims to analyze the level of (in) food and nutritional security of organic family farmers located in the Marrecos community, municipality of Lagoa de Itaenga, Zona da Mata Northern Pernambuco. The research is of qualitative nature, in which he made use of the Brazilian food insecurity (EBIA), and semi-structured questionnaire, which allowed to analyze the specified information of the sampled population. The survey included 8 family groups of the total of 10 which have the Declaration of OCS linked the association so, in which 45 individuals are associated and 13 families participating in organic fairs. From the field and documentary collection (secondary data), some results can be highlighted as: a) the variable schooling: the majority with 55% representation has / is in elementary school, 6% has technical education completed, 6% Superior completed; (b) in relation to gender was identified that most of the public reached by the research is directly or indirectly correspond to the highest percentage for the male representation with a total of 53%; (c) in relation to income, 38% receive up to 2 minimum wages, 25% receive between two to five wages and 25% only a minimum wage, of those receiving social benefit from 38% with a family bag and 25% retirement; (d) participation in the association contributed to the income of families and promoting food security by strengthening families in marketing spaces and through positive change in eating habits; e) While public policies farmers have access to the food acquisition program and national school feeding program as suppliers; f) Family agriculture in Brazil contributes to the supply of internal food, being responsible for the occupation of most labor; g) All those involved in the survey are organic fair and have had their lace altered from involvement with organic agriculture; h) The association contributes with process and strengthening organic agriculture in the Community and the search for marketing spaces; (i) 87% of the groups of farmers interviewed are in a sense of food security according to the second interview; J) The presence of families in a light and moderate food insecurity were identified. From the results obtained in the research it is concluded that the group of organic family farmers located in the Marrecos community, is an atypical example in front of the results published by the FAO that show the hunger index that the population has been meeting, and that this reality has If aggravated with the pandemic, while these family groups of the research were lower impact and remained, they even improved the evaluation indices according to the application of the second stage of EBIA. In this sense, it is concluded that organic agriculture and the associativism system have contributed to the improvement of farmers' lives, and the association is the most viable environment for farmers to organize socially and fight for their rights and access the external opportunities They are emerging, and organic agriculture being the main activity of families in the food and financial matter.